Comparative Assessment of Immunological, Hematological, and Serological Profiles in Type 2 Diabetic and Non-Diabetic Patients: A Matched Case-Control Study - Braim, Sadraldin-Ali; Abdulla Mohammad Amin, Kawa (University of Thi-Qar Journal of Science, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder associated with systemic complications, including hematological and immunological alterations. This study aimed to assess differences in hematological and serological parameters between patients with T2DM and matched non-diabetic controls. A case-control study with matching was conducted between November 17, 2024, and February 2, 2025, at Smart Health Tower–Raparin, Ranya City. There were 176 participants, with 88 patients with type 2 diabetes mellitus and 88 matched healthy controls. Comparative hematological and biochemical marker measurements between the groups were made using the Mann–Whitney U test. Spearman’s rank correlation was used to estimate the correlation of intercellular adhesion molecule-1 and interleukin-31 with different laboratory markers. The chi-square and Fisher tests were used to compare the frequency distribution of abnormalities in the blood film. A p-value < 0.05 was considered significant. T2DM patients had significantly higher levels of HbA1c, fasting blood glucose, CRP, ESR, ICAM-1, IL-31, ferritin, total cholesterol, LDL, triglycerides, VLDL, and lower HDL (all p < 0.01). Morphological abnormalities were significantly more frequent among diabetics. IL-31 showed strong positive correlations with HbA1c (r = 0.68), glucose (r = 0.56), CRP (r = 0.45), and ESR (r = 0.30) (all p < 0.01). ICAM-1 was not significantly correlated with other measured parameters. T2DM is associated with significant hematological and biochemical alterations, including elevated inflammatory markers and abnormal red cell morphology. Regular monitoring of these parameters may aid in the early detection and management of diabetes-related complications.